Isolation and antibacterial activity of diffractic acid compound from lichen Usnea blepharea Motyka - Maulidiyah Maulidiyah, Muhammad Natsir, Wa Nazila, Andi Musdalifah, La Ode Agus Salim, Muhammad Nurdin (Journal of Applied Pharmaceutical Science, 2021)
Lichen’s rich natural resources have been utilized for traditional and herbal medicine. The secondary metabolite compounds of lichen genus Usnea blepharea Motyka have not been reported much. This research was to explore secondary metabolites of lichen U. blepharea Motyka from the mountains in South Sulawesi, Indonesia, and their bioactivity as antibacterials. The powder of lichen was extracted using an acetone solvent and continued separation using gravity column chromatography, preparative thin-layer chromatography, and radial chromatography. Determination of molecular structure was carried out by analyzing the spectral data of UV-Vis, Fourier transform infrared spectroscopy, liquid chromatography-mass spectrophotometer, 1H-NMR (1D-nuclear magnetic resonance), 13C-NMR, and NMR-two-dimensional, including heteronuclear multiple quantum correlation, heteronuclear multiple bond correlation, distortionless enhancement by polarization transfer, and correlated spectroscopy. The isolate of U. blepharea Motyka obtained a diffractic acid compound with molecular formula C20H22O7. The antibacterial bioactivity test showed that the diffractic acid compound actively inhibited (very strongly) the growth of Staphylococcus aureus bacteria at concentrations of 750 and 1,000 ppm with inhibition zones of 14.27 and 17.25 mm, respectively. In addition, Escherichia coli was also actively inhibited (strongly) at concentrations of 750 and 1,000 ppm at 11.00 and 12.75 mm, respectively. This study is interestingly the latest reference source for natural compounds, especially the lichen U. blepharea Motyka, because there have been no reports related to diffractic acid compounds found from this lichen genus and also its strong activity as an antibacterial.
Keywords: Lichen U. blepharea Motyka, diffractic acid, antibacterial, S. aureus, E. coli.